Exploring the Dynamics of Death Attitude Research: A Bibliometric Analysis of Scientific Papers in Dimension (2015-2024) - Karki, Tej Bahadur; D’Mello, Laveena; Neupane, Dasarath; Shrestha, Sajeeb Kumar; Mahat, Dipak (Randwick International of Social Science Journal, 2024)
ABSTRACT Death is not viewed as the absolute end, but rather as a gateway to a continued spiritual existence or rebirth. The main objective of this study is to find out the publication trend of death attitude-related articles from 2015 to 2024. The study used the bibliometric analysis method to analyze the data published in Dimensions. Analysis of death attitude publications over the past decade reveals increasing interest, with a peak in 2021 but a decline in 2022 and 2023. Citation analysis shows a steady rise in citations until 2022, followed by a slight decline. The percentage of publications with citations has decreased over the years. Metrics like FCR and RCR indicate fluctuating citation impact. Interdisciplinary research is evident, with dominant categories including "Human Society," "Health Sciences," and "Law and Legal Studies." Leading countries in death attitude research include the United States, the United Kingdom, and Australia. Challenges such as declining citation uptake underscore the need for enhanced dissemination efforts. Death attitude research has seen increasing interest and impact, significant challenges in citation uptake and fluctuating impact highlight the need for strategic improvements in research dissemination and visibility. Addressing these issues is essential to maintain and enhance the field's scholarly influence.